2014
DOI: 10.1111/bjh.13141
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine profile of patients with chronic immune thrombocytopenia affects platelet count recovery after Helicobacter pylori eradication

Abstract: SummaryHelicobacter pylori eradication induces platelet recovery in a subgroup of patients with chronic immune thrombocytopenia (cITP), but the mechanisms involved are still not understood. We aimed to evaluate the effect of H. pylori eradication on platelet response and to identify the associated serum cytokine profile in 95 patients with cITP. Serum cytokine concentrations were determined by enzyme-linked immunosorbent assay prior to and 6 months after H. pylori eradication. Remission of cITP was observed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 36 publications
2
10
0
2
Order By: Relevance
“…Brito et al [50] reported how H. pylori eradication may determine a platelet response in children and adolescents affected by ITP, while similar results were obtained in other studies [51,52]. Interestingly, Nagata et al [53] demonstrated that a high lymphocyte count may predict the further response to an anti-H. pylori treatment in terms of platelet count, while Rocha et al [54] clearly showed that improvement of ITP after H. pylori eradication may be linked to a more efficient suppression of Thelper (Th) cell 1 and Th17 response and more prominent regulatory T-cell response. Finally, a study by Xie et al, who investigated the hematological response to H. pylori -inoculated Mongolian gerbils, concluded that this infection alone is not sufficient to initiate ITP or IDA, while other factors may possibly participate [55].…”
Section: Idiopathic Thrombocytopenic Purpuramentioning
confidence: 68%
See 1 more Smart Citation
“…Brito et al [50] reported how H. pylori eradication may determine a platelet response in children and adolescents affected by ITP, while similar results were obtained in other studies [51,52]. Interestingly, Nagata et al [53] demonstrated that a high lymphocyte count may predict the further response to an anti-H. pylori treatment in terms of platelet count, while Rocha et al [54] clearly showed that improvement of ITP after H. pylori eradication may be linked to a more efficient suppression of Thelper (Th) cell 1 and Th17 response and more prominent regulatory T-cell response. Finally, a study by Xie et al, who investigated the hematological response to H. pylori -inoculated Mongolian gerbils, concluded that this infection alone is not sufficient to initiate ITP or IDA, while other factors may possibly participate [55].…”
Section: Idiopathic Thrombocytopenic Purpuramentioning
confidence: 68%
“… demonstrated that a high lymphocyte count may predict the further response to an anti‐ H. pylori treatment in terms of platelet count, while Rocha et al. clearly showed that improvement of ITP after H. pylori eradication may be linked to a more efficient suppression of T‐helper (Th) cell 1 and Th17 response and more prominent regulatory T‐cell response. Finally, a study by Xie et al.…”
Section: Hematological Diseasesmentioning
confidence: 99%
“…Recently, Rocha et al reported that platelet response of ITP after eradication of H. pylori was associated with the imbalance correction of T-helper (Th) and T regulatory (Treg) cytokines. 20 This result indicates that the immune responses to H. pylori infected patients with ITP are different, which may be due to the difference between H. pylori strains, e.g. CagA+ and CagA- strains.…”
Section: Discussionmentioning
confidence: 92%
“…A recent study evaluated cytokine levels in patients with chronic ITP before and 6 months after H. pylori eradication. Antibiotic treatment, in patients with a positive platelet response to H. pylori eradication, resulted in a reduction in the cytokine profile consisted with Th1 and Th17 cells; also, there was an enhancement of a Th2 cytokine profile, as well as an increased number of T regulatory cells [52]. Some of the Abs generated during this immune response demonstrate cross-reactivity with host cells, including gastric and duodenal ECs, renal tubular cells, and salivary gland cells [53].…”
Section: Proposed Mechanistic Pathways Of Itp Inductionmentioning
confidence: 99%